The effects of estimated glucose disposal rate and high sensitivity C-reactive protein on risk of incident cardiovascular diseases in middle-aged and elderly Chinese adults: a nationwide prospective cohort study - Linghao Xu; Jiangping Ma; Yong Xu (Lipids in Health and Disease)
Abstract Aim Cardiovascular diseases (CVD) remain the predominant contributor to global mortality and morbidity, necessitating enhanced strategies for primary prevention and early detection. This investigation sought to characterize the associations between estimated glucose disposal rate (eGDR), high sensitivity C-reactive protein (hsCRP), and incident CVD. Methods The research used data from China Health and Retirement Longitudinal Study (CHARLS). The primary exposures included eGDR and hsCRP. Incident CVD served as the primary study endpoint. All statistical analyses were performed utilizing SPSS software (version 25.0) and R software (version 4.4.4). Results The analysis of 7,742 participants revealed incident CVD in 1,981 cases (25.6%), with Kaplan–Meier curves demonstrating significantly elevated cumulative incidence among individuals exhibiting both reduced eGDR and elevated hsCRP levels. Significant interactions were observed between these biomarkers, including an additive effect (relative excess risk due to interaction = 0.09, 95% confidence interval [CI]: 0.03–0.14) and a multiplicative effect (hazard ratio = 1.02, 95% CI: 1.01–1.03). Mediation analyses indicated bidirectional relationships, with eGDR accounting for 5.81% (95% CI: 2.13–9.49%) of the hsCRP-CVD association and hsCRP mediating 8.52% (95% CI: 3.87–13.17%) of the eGDR-CVD relationship. Notably, in individuals with diabetes, the combined predictive capacity of eGDR and hsCRP (area under the curve: 0.645) demonstrated superior discriminative performance compared to either biomarker alone (AUC: 0.645). Conclusion eGDR and hsCRP exert significant joint, interactive and mediating effects on incident CVD in middle-aged and elderly Chinese population. Using eGDR (10.52 mg/kg/min) and hsCRP (1 mg/L) thresholds can be an affordable screening tool in primary care, especially where advanced diagnostics are lacking. Incorporating these assessments into regular check-ups may lower long-term CVD complications and reduce economic burdens.